The role of municipalities in promoting local economic development : a case of Polokwane Municipality, Limpopo Province - Moeketsi, Sebanki Pauline (My University, 2024)
The study investigates the understanding of municipalities in promoting Local Economic Development (LED) in Polokwane Local Municipality. The World Bank (2014: online) defines the concept of LED as a process that offers Local Government, the private and not-for-profit sectors, and local communities the opportunity to work together to improve the local economy. It focuses on enhancing competitiveness, increasing sustainable growth and ensuring that growth is inclusive. LED encompasses a range of disciplines including physical planning, economics and marketing. It also incorporates many local government and private sector functions including environmental planning, business development, infrastructure provision, real estate development and finance. The study adopts a qualitative a qualitative research approach to gain an in-depth understanding of the subject matter. It uses respondents like municipal officials and local economic development beneficiaries. A sample of 10 respondents was selected for the study. The data collection instrument used in the study is interviews. The interviews with the were recorded manually and an audio-taped was used. The data has been analysed using the Thematic analysis which is conducted to identify, organise and report the themes and sub-themes that emerged from the interviews. The study found that local economic development has been introduced globally to achieve four important objectives: to alleviate poverty, to create sustainable jobs, to share important information about government policies and initiatives and to create enabling business environment for investors. Moreover, the findings show that the participants have a common understanding and knowledge of unemployment and poverty. The overall findings show that local economic development interventions contributed to addressing unemployment and poverty in the Polokwane Local Municipality. The study recommends that the municipality invest in research and development, support local businesses, appoint competent personnel and create awareness about the local economic development interventions.
Thesis (MPAM.) -- University of Limpopo, 2024
Keywords: Polokwane Local Municipality; Infrastructure provision; Local Economic Development; Government spending policy; Enterprise zones, Rural; Economic development -- South Africa -- Limpopo; Municipal government -- South Africa -- Limpopo